EFEKTIVITAS DAN EFISIENSI PENGGUNAAN CLINICAL PATHWAYTERHADAP AVERAGE LENGTH OF STAY (AVLOS) PASIEN SECTIO CAESAREA (SC) DI RSI NU DEMAK - Safi’i, Akhmad; Aziz, Abdul; Martani, Anik; Widiastuti, Tri Wahyuni; Wafiroh, Zahrotul (UI Scholars Hub, 2023)
Clinical Pathway (CP) was implemented at the RSI NU Demak Hospital as quality and cost control in health services. One of the quality of services can be seen from the Average Length of Stay (AvLOS), so the implementation of CP is very important to measure its effectiveness and efficiency in reducing AvLOS as well as its efficiency in financing. This study aims to determine the effectiveness and efficiency of using CP for AvLOS as well as its efficiency in financing SC patients at the RSI NU Demak Hospital for the period October 2022-May 2023. The type of this research is qualitative with used case study method. Sample data was done by documentation study in 296 SC patient medical resume document and patient transaction data as well as in-depth interviews with purposive sampling samples. The AvLOS before CP implementation was 5.2 days, after CP implementation (for seven months from November 2022 to May 2023) the AvLOS decreased to 4 days. The average efficiency of SC financing is IDR 874,670.00 (Real Hospital Tariff with LOS of 5.2 days is IDR 7,025,130.00 and with LOS of 4 days is IDR 6,150,460.00) AvLOS before and after the implementation of CP in SC patients at RSI NU Demak Hospital shows its effectiveness as seen from the reduction in AvLOS, as well as having an impact on the efficiency of treatment costs. To further increase the efficiency of financing for SC patients, including the efficiency of drug and disposable material (BHP) packages for SC operations as well as monitoring and evaluating the compliance of medical staff in using CP.